Heterodisulfide Reductase from Acidithiobacilli Is a Key Component Involved in Metabolism of Reduced Inorganic Sulfur Compounds - Levican-Jaque, G (2013)
Heterodisulfide reductase (Hdr), is an iron-sulfur protein which in anaerobic methanogenic archaea catalyzes the reduction of the disulfide bond between coenzyme M and coenzyme B and is coupled to methane formation. In aerobic acidophilic chemolithotrophic bacteria (e.g., biomining bacteria) the function of this enzyme is unclear. Inspection of the genomic sequences of Acidithiobacillus ferrooxidans DSM 16786 and Acidithiobacillus thiooxidans DSM 17318 and reverse transcriptase- PCR results revealed a cluster of six co-transcribed genes, hdrC1, hdrB1, hdrA, orf1, hdrC2 and hdrB2, encoding proteins with high similarity to catalytic Hdr subunits. Additionally, microarray expression profiling and quantitative RT-PCR experiments demonstrated that the hdr genes of At. ferrooxidans and At. thiooxidans were highly expressed when bacteria are grown in the presence of sulfur and tetrathionate. Moreover, hdr genes in At. ferrooxidans were greatly up-regulated when this microorganism was grown in sulfur compared to ferrous medium. These results strongly support a role for Hdr in oxidative metabolism of reduced sulfur compounds in aerobic chemolithotrophic bacteria. © (2013) Trans Tech Publications, Switzerland.